Computer-based accounting systems: The case of manufacturing-based small and medium enterprises in the northern region of Peninsular Malaysia - Ismail, Noor Azizi; Abdullah, Shamsul Nahar; Tayib, Mahamad (Universiti Teknologi Malaysia, 2003)
This study investigates the status of computer-based accounting systems (CBAS) adoption among small and medium manufacturing firms (SMEs) in the northern region of Peninsular Malaysia.Results show that over ninety percent of the firms have adopted CBAS. The adoption of CBAS, however, is still at the beginning stage as majority of the firms only adopted CBAS in the last six years or less and the depth of the CBAS system adopted is behind that of industrialized countries. The results showed that years of adoption are positively correlated with the overall quality of the CBAS adopted.Further investigations on the relationships between CBAS use items and factors that were expected to affect CBAS use indicate that the maturity stage of CBAS adoption was significantly positively correlated with age of business. However, the results did not find evidence supporting previous research that argued age and size of the firms as well as the type of ownership influence the adoption of CBAS.